Human capital quality and stock returns - Bae, Jaewan; Kang, Jangkoo (Journal of Banking & Finance, 2023)
This study investigates the impact of human capital (HC) quality on stock returns. We propose a measure of the quality of HC embedded in firms’ organization capital and show that firms with high-quality HC earn higher future stock returns than firms with low-quality HC, which is not attributable to prevalent risk factors or labor-related factors. The organization capital-to-assets ratio, capturing the relative quantity of organization capital, has significant but limited explanatory power for the return predictability of HC quality. We also confirm the adverse effects of increased HC costs on firm value. These findings are consistent with the argument that firms with higher HC quality have greater exposure to technology frontier shocks due to the risk of key talents leaving.